2017
DOI: 10.7150/jca.20750
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer in Lynch Syndrome Patients

Abstract: Although colorectal cancer (CRC) is the most common cancer type in Lynch syndrome (LS) families, patients have also increased lifetime risk of other types of tumors. The accumulated risk of pancreatic cancer (PC) in LS patients is around 3.7% and developed tumors often present a characteristically medullary appearance with prominent lymphocytic infiltration. LS patients are considered in high risk for PC development as they present 8.6-fold increase compared with the general population.Here we review PC cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…Other extracolonic tumors identified in our LS families, such as pancreatic, prostate, skin and urological cancer, have also been described in other LS populations, with frequencies and risks similar to those described here [ 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionsupporting
confidence: 84%
“…Other extracolonic tumors identified in our LS families, such as pancreatic, prostate, skin and urological cancer, have also been described in other LS populations, with frequencies and risks similar to those described here [ 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionsupporting
confidence: 84%
“…One such context is a specific single gene mutation that predisposes to PDAC. This is known as Hereditary Pancreatic Cancer (HPC) 32 . Another context is predisposition to other cancer types; certain hereditary cancer syndromes, including Hereditary Breast Ovarian Cancer Syndrome (HBOC), Lynch II, Familial Atypical Multiple Mole Melanoma (FAMMM-PC), Peutz-Jegher's and Li Fraumeni syndrome are associated with PDAC.…”
Section: High-risk Groupsmentioning
confidence: 99%
“…Inherited colorectal cancer and endome-trial cancer are frequently seen in Lynch syndrome patients [ 1 ]. Pancreatic adenocarcinoma (PDA) has been associated with Lynch syndrome with an 8.6-fold increase risk compared with the general population [ 2 ]. Previously reported studies showed a cumulative risk of developing pancreatic adenocarcinoma of 3.68% by age 70 years, with cases among families with a history of Lynch syndrome occurring at an earlier age than sporadic cases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%